Where are Compton-thick radio galaxies? A hard X-ray view of three candidates. Issue 4 (8th December 2017) - Ursini, F; Bassani, L; Panessa, F; Bazzano, A; Bird, A J; Malizia, A; Ubertini, P
Abstract: We present a broad-band X-ray spectral analysis of the radio-loud active galactic nuclei NGC 612, 4C 73.08 and 3C 452, exploiting archival data from NuSTAR, XMM–Newton, Swift and INTEGRAL . These Compton-thick candidates are the most absorbed sources among the hard X-ray selected radio galaxies studied in Panessa et al. We find an X-ray absorbing column density in every case below 1.5 × 10 24 cm −2, and no evidence for a strong reflection continuum or iron K α line. Therefore, none of these sources is properly Compton-thick. We review other Compton-thick radio galaxies reported in the literature, arguing that we currently lack strong evidences for heavily absorbed radio-loud AGNs.